Marketing Strategy and Social Influence: How Reference Groups and Internet Marketing Influence Purchasing Decisions Through Brand Image - Muhyidin, Muhyidin Muhyidin; Hafid, Abdul; Mukhbir, Muhammad (Jurnal Bisnis dan Manajemen, 2024)
This study explores the interconnections among reference groups, internet marketing, brand image, and consumer buying decisions, focusing on Gen Z consumers. It investigates how reference groups and internet marketing directly impact purchasing behavior and how brand image mediates these relationships. The research employs a quantitative approach with data collected from a survey of Gen Z respondents, analyzed using structural equation modeling. The findings reveal that both reference groups and internet marketing significantly influence buying decisions. Additionally, brand image is identified as a crucial mediating variable that enhances the effects of reference groups and internet marketing on consumer behavior. High convergent and discriminant validity and reliability of the constructs were confirmed. The study contributes to the understanding of consumer behavior by highlighting the mediating role of brand image and offers practical implications for businesses seeking to optimize their marketing strategies through enhanced brand image and strategic use of reference groups and digital marketing. The results underscore the importance of a strong brand image in leveraging the impact of digital marketing and social influences on consumer purchasing decisions.